Experiences of Being Cared-For: The Perspective of an Expert-by-Experience in Mental Health - Fox, Joanna (Frontiers in Psychiatry, 2022)
It is difficult to understand what it feels like for people with mental ill-health to be cared-for and supported by family members; this experience is often little-explored. Narratives about caring have been increasingly written alongside first-person accounts of recovery, however, there is a dearth of literature written to gain the perspective of being cared-for because of mental distress. Thus, using autoethnography, I present three critical incidents occurring at different points in my recovery to enable exploration of experiences of being cared-for. Firstly, a critical incident at the point of acute unwellness is introduced, secondly an incident during a consultation with a health professional is highlighted, and finally a moment of transition when embarking on an independent life with my husband-to-be is described. I use autoethnography to connect “the autobiographical and personal to the cultural, social, and political”. I consider how the identity of a carer is continually negotiated in a relationship with the service user in both the ‘private’ and the ‘public’ worlds during recovery. I reflect on how professionals can support both service users and carers in a triangle of care, by providing information and support, alongside promoting the development of independence and agency for the service user whilst in the caring relationship. Finally, I introduce a service model which promotes a family network approach to empower the service user, and highlight training programmes on recovery that enable carers. I conclude by suggesting the potential of both approaches to support carers to promote the recovery of the service user.